2012
DOI: 10.2337/dc11-2250
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Dopamine Type 2 Receptor Binding Potential With Fasting Neuroendocrine Hormones and Insulin Sensitivity in Human Obesity

Abstract: OBJECTIVEMidbrain dopamine (DA) neurons, which are involved with reward and motivation, are modulated by hormones that regulate food intake (insulin, leptin, and acyl ghrelin [AG]). We hypothesized that these hormones are associated with deficits in DA signaling in obesity.RESEARCH DESIGN AND METHODSWe assessed the relationships between fasting levels of insulin and leptin, and AG, BMI, and insulin sensitivity index (SI) with the availability of central DA type 2 receptor (D2R). We measured D2R availability us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
137
2
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 136 publications
(155 citation statements)
references
References 40 publications
10
137
2
6
Order By: Relevance
“…That is to say, it is the brain's response to the environment, more so that the environment itself, that dictates the full metabolic outcome of environmental changes such as the presentation of the westernized diet. The neurophysiological literature is now replete with studies demonstrating the important roles of several neural circuits that impact peripheral fuel metabolism (reviewed in [32]) including hypothalamic arcuate-alpha melanocortin-stimulating hormone (αMSH) [33][34][35] and arcuate neuropeptide Y (NPY) -paraventricular nuclei (PVN) circuits [36][37][38], the lateral hypothalamic (LH) leptinorexin mesolimbic circuit [39][40][41][42], ventromedial hypothalamic and arcuate leptin autonomic/neuroendocrine circuits [43][44][45][46][47], and the insulin arcuate [48] and dopamine mesolimbic circuits [49,50] to name just a few. Emerging experimental evidence suggests important roles for the biological clock system residing within and around the SCN of the hypothalamus in the integration of these CNS circuits to create an orchestrated organized CNS output signal (program) to the peripheral organs respecting fuel metabolism (see discussion below) [51][52][53][54].…”
Section: Evolution Of Insulin Resistance and Its Potentiation By The mentioning
confidence: 99%
See 1 more Smart Citation
“…That is to say, it is the brain's response to the environment, more so that the environment itself, that dictates the full metabolic outcome of environmental changes such as the presentation of the westernized diet. The neurophysiological literature is now replete with studies demonstrating the important roles of several neural circuits that impact peripheral fuel metabolism (reviewed in [32]) including hypothalamic arcuate-alpha melanocortin-stimulating hormone (αMSH) [33][34][35] and arcuate neuropeptide Y (NPY) -paraventricular nuclei (PVN) circuits [36][37][38], the lateral hypothalamic (LH) leptinorexin mesolimbic circuit [39][40][41][42], ventromedial hypothalamic and arcuate leptin autonomic/neuroendocrine circuits [43][44][45][46][47], and the insulin arcuate [48] and dopamine mesolimbic circuits [49,50] to name just a few. Emerging experimental evidence suggests important roles for the biological clock system residing within and around the SCN of the hypothalamus in the integration of these CNS circuits to create an orchestrated organized CNS output signal (program) to the peripheral organs respecting fuel metabolism (see discussion below) [51][52][53][54].…”
Section: Evolution Of Insulin Resistance and Its Potentiation By The mentioning
confidence: 99%
“…Dopamine also functions to inhibit feeding in the perifornical area of the hypothalamus and to inhibit sympathetic nervous system (SNS) activation via its actions at the PVN [52,123]. Moreover, positron emission topography scan studies with radiolabeled dopaminergic receptor ligands in humans have identified a decreased dopaminergic function in obese and insulinresistant individuals [49,50]. However, our recent studies suggest that these non-SCN CNS functions of dopamine that collectively tend to maintain the lean/insulin-sensitive state are actually regulated in part by circadian SNC output signals that, as described herein, are modulated by circadian dopaminergic input signals to the SCN.…”
Section: Non-scn Cns Dopaminergic Activities Regulating Peripheral Mementioning
confidence: 99%
“…Prostaglandin E2 may amplify DI and D2 receptor signalling (Kitaoka et al, 2007;Di Marzo and Piomelli, 1992). There is increased D 2 R availability in obese subjects (Dunn et al, 2012) and insulin sensitivity is negatively associated with D 2 R availability. Sustained expression of PGC-Iα in the rat nigrostriatal system selectively impairs dopaminergic function (Ciron et al, 2010) and this and PPAR α (Melis et al, 2011; may synergistically serve to antagonise the essential role of SIRTI (HDAC 3)-FOXO3a signalling in the nucleus accumbens in cocaine and morphine addiction (Ferguson et al, 2013;Ferguson et al, 2015).…”
Section: Dopaminergic Activity In Bipolar Disorder Drug Addiction Ementioning
confidence: 99%
“…Nos EUA, as taxas de sobrepeso e obesidade estão em constante aumento, com cerca de 35% da população adulta de ambos os sexos obesa, enquanto a taxa em adolescentes e crianças obesos chega até 15 a 30% 36 . Isso pôde ser evidenciado no fato de a maioria dos estudos (12 dos 17) ter sido conduzida nos EUA [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] .…”
Section: Métodounclassified
“…Resultado diferente foi encontrado em um estudo conduzido nos EUA: correlação positiva entre a disponibilidade de DRD2 e IMC 34 . A justificativa encontrada pelos autores para este achado diz respeito ao horário em que o estudo foi conduzido.…”
Section: Rev Neurocienc 2014;22(3):373-380unclassified